Comparison between calcium hydroxide mixtures and mineral trioxide aggregate in primary teeth pulpotomy: A randomized controlled trial - Costa E Silva, Lidiane Lucas; Cosme-Silva, Leopoldo [UNESP]; Sakai, Vivien Thiemy; Lopes, Camila Soares; da Silveira, Ana Paula Pereira; Moretti Neto, Rafael Tobias; Gomes-Filho, João Eduardo [UNESP]; Oliveira, Thais Marchini; Moretti, Ana Beatriz da Silveira (FapUNIFESP (SciELO), 2019)
Objectives: To evaluate the effect of calcium hydroxide (CH) associated with two different vehicles as a capping material for pulp tissue in primary molars, compared with mineral trioxide aggregate (MTA). Methodology: Forty-five primary mandibular molars with dental caries were treated by conventional pulpotomy using one of the following materials: MTA only (MTA group), CH with saline (CH+saline group) and CH with polyethylene glycol (CH+PEG group) (15 teeth/group). Clinical and periapical radiographic examinations of the pulpotomized teeth were performed 3, 6, and 12 months after treatment. Data were tested by chi-squared analysis and a multiple comparison post-test. Results: The MTA group showed both clinical and radiographic treatment success in 14/14 teeth (100%), at all follow-up appointments. By clinical evaluation, no teeth in the CH+saline and CH+PEG groups had signs of mobility, fistula, swelling or inflammation of the surrounding gingival tissue. However, in the CH+saline group, radiographic analysis detected internal resorption in up to 9/15 teeth (67%), and inter-radicular bone resorption and furcation radiolucency in up to 5/15 teeth (36%), from 3 to 12 months of follow-up. In the CH+PEG group, 2/11 teeth (18%) had internal resorption and 1/11 teeth (9%) presented bone resorption and furcation radiolucency at all follow-up appointments. Conclusion: CH with PEG performed better than CH with saline as capping material for pulpotomy of primary teeth. However, both combinations yielded clinical and radiographic results inferior to those of MTA alone.
Keywords: Calcium hydroxide; Deciduous tooth; Mineral trioxide aggregate; Pulpotomy; Randomized trial